A comparison of neuroprotective efficacy of newly developed oximes (K203, K206) and commonly used oximes (obidoxime, HI-6) in tabun-poisoned rats - Kassa, Jiri; Karasova, Jana; Vasina, Libor; Bajgar, Jiri; Kuca, Kamil; Musilek, Kamil (Drug and chemical toxicology, 2009)
The neuroprotective effects of newly developed oximes (K203, K206) and commonly used oximes (obidoxime, HI-6) in combination with atropine in rats poisoned with tabun at a sublethal dose (180 microg/kg i.m.; 80% LD(50)) were studied. The tabun-induced neurotoxicity was monitored by using a functional observational battery and an automatic measurement of motor activity. The neurotoxicity of tabun was monitored at 24 hours and 7 days following tabun challenge. The results indicate that K203 and obidoxime in combination with atropine allow all tabun-poisoned rats to survive within 7 days following tabun challenge, while 2 nontreated tabun-poisoned rats and 1 tabun-poisoned rat treated with K206 or HI-6 in combination with atropine died within 7 days. Only one of the newly developed oximes (K203) combined with atropine seems to be effective for a decrease in tabun-induced neurotoxicity within 24 hours after tabun sublethal poisoning, although it is not able to eliminate tabun-induced neurotoxicity completely. On the other hand, the neuroprotective efficacy of commonly used oximes (obidoxime and HI-6), as well as one of the new synthesized oximes (K206), is significantly lower in comparison with K203, according to the number of eliminated tabun-induced neurotoxic signs at 24 hours after tabun challenge. Due to its neuroprotective effects, K203 appears to be a suitable oxime for the antidotal treatment of acute tabun poisonings.
Keywords: Animals; Chemical Warfare Agents; neurotoxické syndromy; Rats, Wistar; Neurotoxicity Syndromes; Organophosphorus Compounds; oximy; chemické bojové látky; organofosforové sloučeniny; Oximes; Male; modely nemocí na zvířatech; Neuroprotective Agents; Obidoxime Chloride; organofosfáty; reaktivátory cholinesterasy; Disease Models, Animal; obidoxim chlorid; krysa rodu Rattus; zvířata; mužské pohlaví; cholinesterasové inhibitory; Cholinesterase Inhibitors; Organophosphates; Rats; Cholinesterase Reactivators; potkani Wistar; neuroprotektivní látky